1988
DOI: 10.1143/jjap.27.l2183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bias Sputtering on W and W-Al Schottky Contact Formation and its Application to GaAs MESFETs

Abstract: The effect of DC bias on the sputter-deposition of W and W-Al on GaAs substrates was investigated. By applying a negative bias to the substrate, the concentration of impurities in the metals and at the interface, such as oxygen, was reduced, and the characteristics of the Schottky contact were improved with respect to the barrier height, the n-value and the uniformity. These results are explained by the reverse sputtering effect for the substrate. This technique was applied to the gate formation of GaAs MESFET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In fact several metallic Fibonacci superlattices have been produced in recent years: Nb/Cu [37][38][39], Mo/V [40], Nb/Ta [41], W/Ti [42] and Ta/Al [43]. We shall concentrate here in the W/Al system, which has been used in Schottky barriers and multilayer systems [44], although no Fibonacci superlattice has been grown to our knowledge. In spite of this fact our choice of the system is guided by several facts.…”
Section: Metallic Systemsmentioning
confidence: 99%
“…In fact several metallic Fibonacci superlattices have been produced in recent years: Nb/Cu [37][38][39], Mo/V [40], Nb/Ta [41], W/Ti [42] and Ta/Al [43]. We shall concentrate here in the W/Al system, which has been used in Schottky barriers and multilayer systems [44], although no Fibonacci superlattice has been grown to our knowledge. In spite of this fact our choice of the system is guided by several facts.…”
Section: Metallic Systemsmentioning
confidence: 99%
“…Indeed, it has now been shown that a variety of conventionally deposited ͑i.e., sputtered or evaporated͒ metallizations, including W-Al, 36 Mo-Al, 37,38 Ta-Al, 39 Ir-Al, 40,41 and Pd-Al, 42 may be utilized to enhance the Schottky barrier height of contacts to n-GaAs. Indeed, it has now been shown that a variety of conventionally deposited ͑i.e., sputtered or evaporated͒ metallizations, including W-Al, 36 Mo-Al, 37,38 Ta-Al, 39 Ir-Al, 40,41 and Pd-Al, 42 may be utilized to enhance the Schottky barrier height of contacts to n-GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Some refractory metal compounds, such as WSi x , WAl x , WN x , TaSi x , TaN x , etc., were proved to be capable of forming Schottky contacts on GaAs, which are stable with annealing temperatures of even up to 800°C. [8][9][10] However, it is difficult to reproducibly control the metal compounds with a specific composition.…”
Section: Introductionmentioning
confidence: 99%